Comparison of Transvaginal Sonographic Doppler Indices Between Normal Intrauterine and Extrauterine Pregnancies Confirmed by Maternal Serum Beta-HCG in the First Trimester of Pregnancy - Tayeba Ali, Raham Bacha, Saira Amin, Syed Muhammad Yousaf Farooq, Mehreen Fatima, Iqra Manzor, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Transvaginal Sonography provides high-resolution images with high reliability and is typically used for the diagnosis of intrauterine pregnancy and ectopic conception. The extra-uterine pregnancy responsible for morbidity and mortality in First Trimester and is 80 percent accounts for maternal death. Doppler ultrasound is a safe and non-invasive technique in the evaluation of uterine artery flow patterns. It can calculate the indices like Resistivity index and Pulsatility index in numerical value. It is also observed that there are changes noted between the uterine artery indices in normal intrauterine and extrauterine pregnancies. However, it is important to compare them in normal intrauterine and extrauterine pregnancies. Objective: To compare the trans-vaginal sonographic Doppler indices of the uterine artery between normal and ectopic pregnancies confirmed by maternal serum Beta-hCG. Methodology: This case-control study was conducted at Shireen Ultrasound Clinic Peshawar, KPK Pakistan. This study enrolled a purposive sample of 80 (40 ectopic & 40 intrauterine) pregnant female patients with age 18 to 45 years. The examination was performed with Toshiba Nemio 20(Xario Prime with TVS Probe frequency range 7-14MHz). The Resistive index, Pulsatility index, mean and standard deviation were calculated for the continuous variables. Results: In normal early pregnancy, the mean RI of the right uterine artery was 0.53±0.10 and the mean RI of the left uterine artery was 0.52±0.07. In the cases of (ectopic pregnancy), the mean RI of the right uterine artery was 0.73±0.08 and the mean RI of the left uterine artery was 0.78±0.10. The p-value of the right and left uterine arteries in normal intrauterine and extrauterine ectopic pregnancies were significant at 0.05 level. Conclusion: The resistivity index of uterine arteries is significantly high in ectopic conceptions than in normal intrauterine pregnancies. But there was no significant change in PI of normal intrauterine and ectopic pregnancies. Keywords: adnexal mass, ectopic pregnancy, Transvaginal ultrasound, tubal pregnancy.